PHYS 510 A: Mathematical Methods of Physics Homework #1 Kristin Kathleen Creech Lassonde

1

1
1.1

Vector Analysis
Definitions, Elementary Approach

Exercise 1.1 Show how to find A and B, given A + B and A − B. Answer To find A simply sum them and divide by two componentwise. To find B simply subtract them and divide by two componentwise. Define the vectors C and D:

C=A+B D=A−B Then:

A= = = = =

C+D 2 (A + B) + (A − B) 2 A+B+A−B 2 A+A+B−B 2 2A 2

=A Also:

2

B= = = = =

C−D 2 (A + B) − (A − B) 2 A+B−A+B 2 A−A+B+B 2 2B 2

=B

3

is defined by the equation vrel = vA − vB . where vA is the velocity of A and vB is the velocity of B. Determine the velocity of A relative to B if vA = 30 km/hr east vB = 40 km/hr north. vrel . Answer See Figure.4 The velocity of sailboat A relative to sailboat B. 4 .Exercise 1.

so that vrel = vA − vB = 30i − 40j.1◦ south of east. we find the magnitude of vrel : vrel = = 302 + (−40)2 √ 900 + 1600 √ = 2500 = 50 km/hr We then find the angle: sin θ = −vB vrel −40 = 50 4 5 =⇒ θ = sin−1 ≈ 0.1◦ South of East Answer: vrel = 50 km/hr 53. 5 . Now.9272 Radians ≈ 53.We have vA = 30i and vB = 40j.

In terms of A. A. etc. 6 . B. show that the vector sum of the successive sides of the triangle (AB + BC + CA) is zero. where the side AB is from A to B. and C that extend from the origin. and C.Exercise 1.8 A triangle is defined by the vertices of three vectors. Answer See Figure. B.

Then. BC the vector from B to C.Let AB be the vector from A to B. CA be the vector from C to A. A + AB = B =⇒ AB = B − A B + BC = C =⇒ BC = C − B C + CA = A =⇒ CA = C − B Then AB + BC + CA = (B − A) + (C − B) + (A − C) =B−A+C−B+C−B =A−A+B−B+C−C =0 7 .

(a) Write out the algebraic equation for the sphere. a.Exercise 1. y1 . Answer For r1 = (x1 . then the sphere is: (x − x1 )2 + (y − y1 )2 + (z − z1 )2 = a2 (b) Write out a vector equation for the sphere.9 A sphere of radius a is centered at a point r1 . 8 . Answer r = r1 + a (r − r1 )2 = a2 =⇒ r − r1 = a =⇒ r = r1 + a a takes on all directions but has a fixed magnitude. z1 ).

1 (a) Show that the magnitude of a vector A. (A2 + A2 ) 2 = (A x + A y ) 2 x y independent of the rotation angle ϕ. 9 .2 Advanced Definitions Exercise 2. 1 1 2 2 1 Answer See Figure. A = (A2 + A2 ) 2 is independent of the y x orientation of the rotated coordinate system.1. This independence of angle is expressed by saying that A is invariant under rotations.

adding them together: 10 .First. Ax = Ax cos ϕ + Ay sin ϕ Ay = −Ax sin ϕ + Ay cos ϕ Squaring Ax and Ay . we obtain: (Ax )2 = (Ax cos ϕ + Ay sin ϕ)2 = (Ax cos ϕ + Ay sin ϕ)(Ax cos ϕ + Ay sin ϕ) = A2 cos2 ϕ + 2Ax Ay cos ϕ sin ϕ + A2 sin2 ϕ x y (Ay )2 = (−Ax sin ϕ + Ay cos ϕ)2 = (−Ax sin ϕ + Ay cos ϕ)(−Ax sin ϕ + Ay cos ϕ) = A2 sin2 ϕ − 2Ax Ay sin ϕ cos ϕ + A2 cos2 ϕ x y Then. x = x cos ϕ + y sin ϕ y = −x sin ϕ + y cos ϕ Then.

(Ax )2 + (Ay )2 = (A2 cos2 ϕ + 2Ax Ay cos ϕ sin ϕ + A2 sin2 ϕ) x y + (A2 sin2 ϕ − 2Ax Ay sin ϕ cos ϕ + A2 cos2 ϕ) y x = A2 cos2 ϕ + A2 sin2 ϕ + A2 sin2 ϕ + A2 cos2 ϕ x y x y = (A2 sin2 ϕ + A2 cos2 ϕ) + (A2 sin2 ϕ + A2 cos2 ϕ) y x x y = A2 (sin2 ϕ + cos2 ϕ) + A2 (sin2 ϕ + cos2 ϕ) x y = A2 + A2 x y =⇒ (Ax )2 + (Ay )2 = A2 + A2 x y 11 .

that is. as in terms of its unprimed components. Ax = Ax cos ϕ + Ay sin ϕ Ay = −Ax sin ϕ + Ay cos ϕ   Ax Ay   = cos ϕ sin ϕ   Ax Ay   − sin ϕ cos ϕ Now. α = α − ϕ. Again. y) A defines an angle α relative to the positive x-axis and α relative to the positive x -axis. we will need to use:       Ax Ay = A cos α A sin α 12 . Show that A = A defines the same direction in space when expressed in terms of its primed components. The angle from x to x is ϕ.(b) At a given point (x. begin with: x = x cos ϕ + y sin ϕ y = −x sin ϕ + y cos ϕ Then. Answer See Figure above.

  Ax Ay   =  =  =  =  cos ϕ sin ϕ     Ax Ay         − sin ϕ cos ϕ cos ϕ sin ϕ A cos α A sin α − sin ϕ cos ϕ A cos α cos ϕ + A sin α sin ϕ −A cos α sin ϕ + A sin α cos ϕ A(cos α cos ϕ + sin α sin ϕ) −A(cos α sin ϕ + sin α cos ϕ)  A cos(α − ϕ)  = −A sin(α − ϕ)   A cos α  = −A sin α =⇒ α = α − ϕ 13 .

Find the surface swept out by the tip of r if (a) (r − a) · a = 0.3 Scalar or Dot Product The vector r. starting at the origin. terminates at and specifies the Exercise 3. The vector a is constant (constant in magnitude and direction) 14 . z).1.3 point in space (x. y.

15 .(b) (r − a) · r = 0. The vector a is constant (constant in magnitude and direction).

16 . Answer See Figure below. A2 = (B − C)2 =⇒ A · A = (B − C) · (B − C) =⇒ A2 = B · B − B · C − C · B + C · C A2 = B · B − B · C − B · C + C · C A2 = B · B − 2B · C + C · C A2 = B · B + C · C − 2B · C A2 = B 2 + C 2 − 2BC cos θ where θ is the angle between B and C.4 Vector or Cross Product Exercise 4.1.2 Prove the law of cosines starting from A2 = (B − C)2 .

Q = −6i − 4j + 2k. find two that are perpendicular and two that are parallel or antiparallel. R = i − 2j − k. we simply find two with a dot product of zero: Perpendicular P ⊥ R P · R = (3)(1) + (2)(−2) + (−1)(−1) =3−4+1 =0 17 .5 Given the three vectors: P = 3i + 2j − k. Answer To find two vectors that are perpendicular.Exercise 4.

we simply find two that are a scalar multiple of one another: Parallel or Antiparallel P Q They are antiparallel since the scalar multiple is negative. (−2)P = (−2)(3i + 2j − k) = −6i − 4j + 2k =Q 18 .To find two vectors that are parallel or antiparallel. so the vectors are in opposite directions.

7 Prove that (A × B) · (A × B) = (AB)2 − (A · B)2 Answer Begin with the definition of cross product that A × B = AB sin θ. (A × B) · (A × B) = (A × B)2 = (AB sin θ)2 = (AB)2 sin2 θ = (AB)2 (1 − cos2 θ) = (AB)2 − (AB)2 cos2 θ = (AB)2 − (AB cos θ)2 = A2 B 2 − (A · B)2 19 . where θ is the angle between A and B. and Pythagorean Identity sin2 θ + cos2 θ = 1 in the form sin2 θ = 1 − cos2 θ.Exercise 4. where θ is the angle between A and B. We will also use the definition of dot product that A · B = AB cos θ.

b. Thus. it follows that e ⊥ a and f ⊥ a. then the angle between e and f . 20 . and d all lie in the same place. c. Then. It is given that e × f = 0.10 If four vectors a. ef sin θ = 0. show that (a × b) × (c × d) = 0 Hint: Consider the directions of the cross-product vectors. To have this. Answer Let e = a × b and f = c × d. we have that e and f must be either parallel or antiparallel.Exercise 4. θ must be either 0◦ or 180◦ .

= j − 2i q v = i.16 The magnetic induction B is defined by the Lorentz force equation F = q(v × B) Carrying out three experiments. calculate the magnetic induction B.Exercise 4. 21 . = 4i − k q F v = k. From the results of these three separate experiments. we find that if F = 2k − 4j q F v = j.

2 Verify the expansion of the triple vector product A × (B × C) = B(A · C) − C(A · B) by direct expansion in cartesian coordinates. Answer i j k B × C = Bx By Bz Cx Cy Cz =i By Bz Cy Cz −j Bx Bz Cx Cz +k Bx By Cx Cy =i(By Cz − Bz Cy ) − j(Bx Cz − Bz Cx ) + k(Bx Cy − By Cx ) =i(By Cz − Bz Cy ) + j(Bz Cx − Bx Cz ) + k(Bx Cy − By Cx ) 22 .1.5 Triple Scalar Product. Triple Vector Product Exercise 5.

i A × (B × C) = Ax j Ay k Az (By Cz − Bz Cy ) (Bz Cx − Bx Cz ) (Bx Cy − By Cx ) =i Ay Az −j Ay Ax Az (Bz Cx − Bx Cz ) (Bx Cy − By Cx ) +k Ax (By Cz − Bz Cy ) (Bx Cy − By Cx ) (By Cz − Bz Cy ) (Bz Cx − Bx Cz ) =i[Ay (Bx Cy − By Cx ) − Az (Bz Cx − Bx Cz )] − j[Ax (Bx Cy − By Cx ) − Az (By Cz − Bz Cy )] + k[Ax (Bz Cx − Bx Cz ) − Ay (By Cz − Bz Cy )] =i[Ay Bx Cy − Ay By Cx − Az Bz Cx + Az Bx Cz ] − j[Ax Bx Cy − Ax By Cx − Az By Cz + Az Bz Cy ] + k[Ax Bz Cx − Ax Bx Cz − Ay By Cz + Ay Bz Cy ] =i[Ay Bx Cy − Ay By Cx − Az Bz Cx + Az Bx Cz ] + j[−Ax Bx Cy + Ax By Cx + Az By Cz − Az Bz Cy ] + k[Ax Bz Cx − Ax Bx Cz − Ay By Cz + Ay Bz Cy ] A · C = Ax Cx + Ay Cy + Az Cz 23 .

B · (A · C) =Bx (Ax Cx + Ay Cy + Az Cz )i + By (Ax Cx + Ay Cy + Az Cz )j + Bz (Ax Cx + Ay Cy + Az Cz )k =(Ax Bx Cx + Ay Bx Cy + Az Bx Cz )i + (Ax By Cx + Ay By Cy + Az By Cz )j + (Ax Bz Cx + Ay Bz Cy + Az Bz Cz )k A · B = Ax Bx + Ay By + Az Bz C · (A · B) =Cx (Ax Bx + Ay By + Az Bz )i + Cy (Ax Bx + Ay By + Az Bz )j + Cz (Ax Bx + Ay By + Az Bz )k =(Ax Bx Cx + Ay By Cx + Az Bz Cx )i + (Ax Bx Cy + Ay By Cy + Az Bz Cy )j + (Ax Bx Cz + Ay By Cz + Az Bz Cz )k 24 .

comparing the two: 25 .B · (A · C) − C · (A · B) =(Ax Bx Cx + Ay Bx Cy + Az Bx Cz )i + (Ax By Cx + Ay By Cy + Az By Cz )j + (Ax Bz Cx + Ay Bz Cy + Az Bz Cz )k + (−Ax Bx Cx − Ay By Cx − Az Bz Cx )i + (−Ax Bx Cy − Ay By Cy − Az Bz Cy )j + (−Ax Bx Cz − Ay By Cz − Az Bz Cz )k =(Ay Bx Cy + Az Bx Cz )i + (Ax By Cx + Az By Cz )j + (Ax Bz Cx + Ay Bz Cy )k + (−Ay By Cx − Az Bz Cx )i + (−Ax Bx Cy − Az Bz Cy )j + (−Ax Bx Cz − Ay By Cz )k =(Ay Bx Cy + Az Bx Cz − Ay By Cx − Az Bz Cx )i + (Ax By Cx + Az By Cz − Ax Bx Cy − Az Bz Cy )j + (Ax Bz Cx + Ay Bz Cy − Ax Bx Cz − Ay By Cz )k Now.

A × (B × C) =i[Ay Bx Cy − Ay By Cx − Az Bz Cx + Az Bx Cz ] + j[−Ax Bx Cy + Ax By Cx + Az By Cz − Az Bz Cy ] + k[Ax Bz Cx − Ax Bx Cz − Ay By Cz + Ay Bz Cy ] B · (A · C) − C · (A · B) =(Ay Bx Cy + Az Bx Cz − Ay By Cx − Az Bz Cx )i + (Ax By Cx + Az By Cz − Ax Bx Cy − Az Bz Cy )j + (Ax Bz Cx + Ay Bz Cy − Ax Bx Cz − Ay By Cz )k A × (B × C) = B · (A · C) − C · (A · B) 26 .

where p is the linear momentum. B = ω. In section 4. Applying the property.Exercise 5. For r · ω = 0 this reduces to L = Iω. Answer L=r×p = r × mv = m[r × v] = m[r × ω × r] From the previous problem. With linear and angular velocity related by v = ω × r.5 The angular momentum L of a particle is given by L = r × p = mr × v. we get: r × (ω × r) = ω · (r · r) − r · (r · ω) So we have: 27 . we have: A × (B × C) = B · (A · C) − C · (A · B) Here.6 this result is generalized to form an inertia tensor. show that: L = mr2 [ω − ˆ(ˆ · ω)] rr Here ˆ is a unit vector in the r direction. and C = r. we have A = r. with r the moment of inertia I given by mr2 .

L = m[r × ω × r] = m[ω · (r · r) − r · (r · ω)] = m[ω · r2 − r · (r · ω)] = m[ω · r2 − rˆ · (rˆ · ω)] r r = m[ω · r2 − r2ˆ · (ˆ · ω)] r r = mr2 [ω − ˆ · (ˆ · ω)] r r 28 .

2 Answer 1 T = m(r × ω)2 2 1 = m(rω sin θ)2 2 1 = m(rω)2 sin2 θ 2 1 = m(rω)2 (1 − cos2 θ) 2 1 = m[(rω)2 − (rω)2 cos2 θ] 2 1 = m[(rω)2 − (rω cos θ)2 ] 2 1 = m[(rω)2 − (r · ω)2 ] 2 1 = m[r2 ω 2 − (r · ω)2 ] 2 29 .Exercise 5. Show that: 2 1 T = m[r2 ω 2 − (r · ω)2 ] 2 For r · ω = 0 this reduces to T = 1 Iω 2 with the moment of inertia I given by mr2 .6 The kinetic energy of a single particle is given by T = 1 mv 2 . For 2 rotational motion this becomes 1 m(r × ω)2 .

we have: A × (B × C) = B · (A · C) − C · (A · B) This gives us that: a × (b × c) = b · (a · c) − c · (a · b) b × (c × a) = c · (b · a) − a · (b · c).7 Show that a × (b × c) + b × (c × a) + c × (a × b) = 0. c × (a × b) = a · (c · b) − b · (c · a). Then. 30 .Exercise 5. and. Answer From the previous problem.

a × (b × c) + b × (c × a) + c × (a × b) =(b · (a · c) − c · (a · b)) + (c · (b · a) − a · (b · c)) + (a · (c · b) − b · (c · a)) =(b · (a · c) − c · (a · b)) + (c · (a · b) − a · (b · c)) + (a · (b · c) − b · (a · c)) =(b · (a · c) − b · (a · c)) + (c · (a · b) − c · (a · b)) + (a · (b · c) − a · (b · c)) =0 31 .

z) = (x2 + y 2 + z 2 )− 2 .1. 2. 32 .6 Gradient 3 Exercise 6. 3).1 If S(x. find (a) S at the point (1. y.

and 33 . 2. | S| at (1.(b) the magnitude of the gradient of S. 3).

3).(c) the direction cosines of S at (1. 2. 34 .

show that dF = (dr · )F + ∂F dt.4 If a vector function F depends on both space coordinates (x. ∂t 35 .Exercise 6. y. z) and time t.

Sign up to vote on this title
UsefulNot useful